Resíduos de processamento de jundiá (Rhamdia quelen) e seu valor nutricional em dietas para peixes - Rossato, Suzete (2012)
The aim of this study was to evaluate the use of processing waste and discard of jundiá used in the diet of this species, verifying its influence on growth, serum biochemistry, liver and digestive parameters. In the first experiment, 50 fish per experimental unit were used (initial weight = 5.53 ± 0.09 g). Four diets were tested: control, composed of 30% swine meat and bone meal (FCO); diet composed of 30% jundiá whole fish meal (FJPI); diet composed of 30% jundiá carcasses with viscera meal (FCJCV), and diet composed of 30% jundiá carcasses without viscera meal (FCJSV). In the second experiment, the diets tested different levels of FCJCV (0, 3.75, 7.5, 15, and 30%). Thirty fish per experimental unit were used (initial weight = 7.2 ± 0.27 g). We collected data on weight, condition factor, specific growth rate, feed conversion, daily weight gain, and protein retention rate. We also analyzed serum biochemistry, liver, intestinal and stomach parameters. In the first experiment, we observed higher final weight, daily weight gain, specific growth rate, feed conversion, and deposition of body protein with the FCJCV treatment. In the second experiment, the inclusion of 30% FCJCV promoted higher weight gain, specific growth rate, feed conversion, and body protein deposition. The incorporation of processing waste meal of jundiá in the diet altered serum biochemistry, liver and digestive parameters, but did not influence the fish growth. A higher growth of jundiá juveniles was observed with the inclusion of 30% FCJCV in the diet